Gender Undertone in Occupational Competence of University Workers. An Application of Holand’s Theory (1959) - Arijesuyo, Amos. E.; Olufemi, Adodo Sunday (Richtmann Publishing, 2012)
This survey research investigated gender undertone in occupational of selected university workers. The participation comprisetwo hundred and forty (240) male and female senior non-academic and academic university workers selected through stratified randomtechnique from the Federal University of Technology, Akure and Adekunle Ajasin University Akungba Akoko, Ondo state. The modifiedself-directed search (SDS) developed by Holland (1985) was adopted for the study. The results showed that male workers weresignificantly higher in realistic, investigative, enterprising and artistic competences while female workers faired better in social andconforming competences.